Robust Lean Management model for maintenance in Iraqi oil and gas industry: A review study - Al Hussien Mokhef Al Kitab M.A.; Al-Nuaimi F.B.I.; Ansari M.N.M.; Ibrahim T.K. (Bangladesh University of Engineering and Technology, 2023)
Lean Management (LM) is a business process strategy employed by many companies to improve productivity in business and manufacturing issues. Lean production is aimed at improving productivity and efficiency in numerous industrial enterprises via a flexible implementation process that is primarily based on proper management and waste reduction. Most enterprises rely on lean approach to improve productivity, eliminate inventory, and deliver quality products. This paper provides a comprehensive review on the usage of lean approach in the oil and gas (O&G) industry as they are the main energy source for the production and transportation of goods and services. In addition, this study investigates whether lean approaches could enhance the maintenance performance of O&G companies by reviewing the lake of applications to LM maintenance approach in O&G productions, especially in Iraq. 2021 Zibeline International Publishing Sdn. Bhd.. All rights reserved.